Gender Diversity Of Leaders On Organizational Performance Through Organizational Culture - Muhamad Alwi; Hunik Sri Runing Sawitri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Objectives - The purpose of this paper is to examine the philosophical aspects, namely the construction of organizational culture which has been the concern of scientists in the fields of human resource management, psychology, and anthropology. Design/methodology/approach – This paper uses a literature study approach by mapping previous research related to organizational culture in articles, Scopus indexed journals and Google Scholar over the last five decades. Findings – The antecedents of organizational culture can come from internal factors and external factors such as a sense of achievement and company policies. From the organizational culture are organizational performance, job satisfaction, job performance, and company strategy. Originality – The purpose of this paper is to propose a schematic research model that shows the influence of organizational culture on organizational performance can be moderated by the gender diversity of employees. Keywords - Philosophy of Science, Organizational Culture Type of Writing – Concept writing